Prediction and Treatment of Water Leakage Risk Caused by the Dynamic Evolution of Ground Fissures in Gully Terrain - Feng, Dong; Hou, Enke; Xie, Xiaoshen; Che, Xiaoyang; Hou, Pengfei; Long, Tianwen (Frontiers in Earth Science, 2022)
Surface water leakage damage in the loess gully terrain is one of the main hazards of coal seam mining in shallow burial depth. The burial depth of the 5-2 coal seam in the area where the study area gully is located is less than 50m from the surface. The fissures that expand upward after mining are easy to penetrate the surface to form water-conducting channels. There is a potential risk of surface water leakage during rainy periods. Therefore, a typical U-shaped gully to work in the northern Shaanxi coal mine was adopted as the study area’s face using “multi-mark fixed-point measurement” and on-site measurement by UAV aerial photography to reveal the characteristics of plane development and dynamic evolution process of gully surface fissures. Based on the experimental platform for surface fissure leakage developed and designed by the team, the indoor test model corresponding to the actual situation was established, and the mathematical models of channel actual flood water inrush volume, channel fissure width, and channel flood flow were established. The actual mine water flow and the mine drainage capacity were compared and analyzed, and the division standard of gully mining surface fissure collapsed water hazard was proposed, providing a theoretical reference for the prediction of fissure leakage hazard zoning in surface gullyes of shallow buried coal seams. According to the development height of the water-conducting fissure zone (WCFZ), the treatment methods of surface fissures in gullies under different security conditions were designed, and the field application was carried out with good results. The results showed that the treatment methods in this paper could effectively prevent the surface fissures leakage in gullies.